Pengaruh Literasi Keuangan terhadap Perilaku Keuangan dengan Kelompok Generasi sebagai Mediasi dan Moderasi - Mochammad Rizaldy Insan Baihaqqy (Coopetition : Jurnal Ilmiah Manajemen, 2022)
A country's economy is largely determined by public awareness of financial literacy, because it has an impact on its financial behavior, on a micro level this has implications for the level of welfare in the family and macro has implications for increasing national economic growth. The purpose of this study is to examine financial literacy on financial behavior in the generation group. This study uses a quantitative approach with survey methods, data analysis using conditional processes. The results showed that the generation group was able to mediate and moderate financial literacy on financial behavior ,this indicates that it is important for each generation group to continuously improve financial literacy in order to have good financial behavior.